The Effect Of Work Discipline And Employee Loyalty On Employee Performance Of The HR & General Department Of PT. Semen Padang - Febriani, Rina; Hendri, Sri Rahmasari (Adpebi Science Series, 2024)
This study aims to determine the influence of work discipline and employee loyalty on employee performance of the Department of Human Resources & General Affairs of PT. Semen Padang. This type of research is a causal associative type. The population of this study refers to all employees of the Department of Human Resources & General Affairs of PT. Semen Padang is 60 employees. The determination of the number of samples in this study uses a saturated sampling technique, so that the sample of this study is all employees in the Department of Human Resources & General Affairs of PT. Semen Padang. The results of the t-test showed thatwork discipline with a ttable > ttable value or 2,430 > 1,672 with a significant value of 0.018 < 0.05, that work discipline had a positive and significant effect on the performance of employees of the Department of Human Resources & General Affairs of PT. Semen Padang. The results of the t-test of employee loyalty variables with a t-count value of > ttable or 6.449 > 1.672 with a significant value of 0.000 < 0.05, that employee loyalty has a positive and significant effect on the performance of employees of the Department of Human Resources & General Affairs of PT. Semen Padang. The results of the F test are known to have a value of 29,016 and a value of 3.15with a significant value of 0.000 < 0.05. This result means that together (simultaneously) the variables of work discipline and employee loyalty have an influence and significantly on the performance of employees of the Department of Human Resources & General Affairs of PT. Semen Padang.